2014
DOI: 10.1021/jf503839m
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Isoflavonoids by Astragalus membranaceus Hairy Root Cultures and Evaluation of Antioxidant Activities of Extracts

Abstract: In this study, Astragalus membranaceus hairy root cultures (AMHRCs) were established as an attractive alternative source for the efficient production of isoflavonoids (IF). A. membranaceus hairy root line II was screened as the most efficient line and was confirmed by PCR amplification of rolB, rolC and aux1 genes. Culture parameters of AMHRCs were systematically optimized, and five main IF constituents were quali-quantitatively determined by LC-MS/MS. Under optimal conditions, the total IF accumulation of 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 39 publications
1
54
0
Order By: Relevance
“…In this study hypocotyls were found to be the most responsive tissue for infection. The hairy root system is very interesting for the production of secondary metabolites in medicinal plants ( Jiao et al, 2014 ; Patra and Srivastava, 2014 ; Wawrosch et al, 2014 ; Gai et al, 2015 ; Tian, 2015 ) or to engineer model plants to secrete industrially valuable metabolites. For example, in tobacco transgenic hairy roots the production of THCA was successfully obtained by expressing hemp THCAS ( Sirikantaramas et al, 2007 ).…”
Section: Cannabis Biotechnology: Challenges and Prospectsmentioning
confidence: 99%
“…In this study hypocotyls were found to be the most responsive tissue for infection. The hairy root system is very interesting for the production of secondary metabolites in medicinal plants ( Jiao et al, 2014 ; Patra and Srivastava, 2014 ; Wawrosch et al, 2014 ; Gai et al, 2015 ; Tian, 2015 ) or to engineer model plants to secrete industrially valuable metabolites. For example, in tobacco transgenic hairy roots the production of THCA was successfully obtained by expressing hemp THCAS ( Sirikantaramas et al, 2007 ).…”
Section: Cannabis Biotechnology: Challenges and Prospectsmentioning
confidence: 99%
“…T-DNA carries the rol genes (rolA, rolB, rolC, and rolD), which together or separately cause the hairy root syndrome in host plants at sites of infection (White et al 1985). Transgenic hairy roots were shown to stably produce secondary metabolites at levels comparable to or greater than those of the intact plants (Swain et al 2012;Oksman-Caldentey and Hiltunen 1996;Giri and Narasu 2000;Grzegorczyk et al 2006;Tiwari et al 2008;Sheela 2012;Jiao et al 2014;Bansal et al 2014;Gai et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Therefore, the mobile phase composition was simplied using an acetonitrile-water mixture for all analytes in this work. Optimization of LC conditions.…”
Section: Establishment Of Lc-ms/ms Methodsmentioning
confidence: 99%
“…Optimization of LC conditions. 9 For the simultaneous determination of all target analytes, the ESI-MS/MS with negative-ion mode was eventually chosen to analyze the eleven target compounds in spite of sacricing the detection sensitivity of astragalosides. According to our previous report, the acetonitrile-water mobile phase is the best choice for the separation and ionization of astragalosides and isoavonoids.…”
Section: Establishment Of Lc-ms/ms Methodsmentioning
confidence: 99%
See 1 more Smart Citation